2021
DOI: 10.1093/neuros/nyab062
|View full text |Cite
|
Sign up to set email alerts
|

Are Guidelines Important? Results of a Prospective Quality Improvement Lumbar Fusion Project

Abstract: BACKGROUND United States (U.S.) healthcare is a volume-based inefficient delivery system. Value requires the consideration of quality, which is lacking in most healthcare disciplines. OBJECTIVE To assess whether patients who met specific evidence-based medicine (EBM)-based criteria preoperatively for lumbar fusion would achieve higher rates of achieving the minimal clinical important difference (MCID) than those who did not m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…[11][12][13][14] Surgical decision-making concerning revision of lumbar fusion is controversial, with recent studies suggesting that revisions supported by evidence-based criteria were associated with better functional outcomes. 14,15 The most common indications for revisions are postlaminectomy syndrome, adjacent segment degeneration (ASD), and pseudarthrosis. 11 Pseudarthrosis was found to be the most common cause of revision lumbar surgery, responsible for 31% of revision cases.…”
mentioning
confidence: 99%
“…[11][12][13][14] Surgical decision-making concerning revision of lumbar fusion is controversial, with recent studies suggesting that revisions supported by evidence-based criteria were associated with better functional outcomes. 14,15 The most common indications for revisions are postlaminectomy syndrome, adjacent segment degeneration (ASD), and pseudarthrosis. 11 Pseudarthrosis was found to be the most common cause of revision lumbar surgery, responsible for 31% of revision cases.…”
mentioning
confidence: 99%
“…Prior analysis found significant predictors and/or meaningful confounders of 6-month MCID in ODI to include NASS concordance, preoperative ODI, ASA, and revision surgery; which were included in multivariable analysis. 29 Multivariable logistic regression analysis reaffirmed the significant predictive value of the variables previously described. The most optimal regression model (Table 2) included only statistically significant variables predicting MCID in ODI-NASS Concordance (P = 0.0441), preoperative ODI (P < 0.0001), ASA Class (P = 0.0063), classification as a revision surgery (P = 0.0004)-and the principal variable of interest: Attending surgeon (Wald χ 2 = 43.68, P < 0.0001; R 2 = 73.7%).…”
Section: Resultsmentioning
confidence: 55%
“…As seen in previous literature, patient specific factors such as preoperative ODI, ASA class, and classification of revision surgery demonstrated statistical correlations with PRO in the form of MCID at 6 months postoperatively. 29,34 Of note, patient factors traditionally predictive of increased morbidity such as age, 35 BMI, 36 and smoking status 37 did not improve outcome modeling as they did not significantly contribute to differences in PRO in this cohort. This is likely When examining surgeon experience, this study confirmed that MCID in ODI improvements postoperatively were statistically correlated with the surgeon's years in practice.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…[1][2][3] Despite the increasing utilization of instrumented fusion for the treatment of lum-bar pathology, there is still a lack of medical literature detailing concrete fusion indications and studies validating guidelines as predictors of outcomes. [4][5][6] This is largely secondary to heterogeneity in clinical decision-making amongst spine surgeons and surgical indications in lumbar spine pathology management.…”
Section: Introductionmentioning
confidence: 99%